Analysis of Rice Farming Using Jajar Legowo and Coventional Planting System in Muaro Sebo District, Muaro Jambi Regency - Yulistio Nadeak, Rio; Edison, Edison; Oktari Ulma, Riri (Program Studi Agribisnis bekerja sama dengan PERHEPI, 2026)
This research aims to: (1) describe the general characteristics of lowland rice farming under the jajar legowo and conventional planting systems in Maro Sebo District, Muaro Jambi Regency; (2) determine farmers’ income under both planting systems; and (3) analyze the income differences between the jajar legowo and conventional systems. The research employed a survey method, with primary data collected through interviews with respondent farmers. Descriptive analysis was used to illustrate the conditions of lowland rice farming under both planting systems, while quantitative analysis was conducted to examine farmers’ income levels. The results show that: (1) the jajar legowo system requires greater production inputs—including seeds, fertilizers, pesticides, and labor—compared with the conventional system, yet it yields a higher volume of harvested dry grain (GKP). (2) Farmers’ income under the jajar legowo system is higher than that under the conventional planting system. (3) Based on the results of the ANOVA test, there is a statistically significant difference in farmers’ income between the two planting systems, indicating that the jajar legowo system provides a higher income than the conventional system. Overall, the findings suggest that although the jajar legowo planting system demands more intensive input use, it delivers higher production and income, making it a more advantageous option for lowland rice farmers in Maro Sebo District.